Endocrine Crosstalk Between Skeletal Muscle and the Brain - Delezie, Julien; Handschin, Christoph (Frontiers in Neurology, 2018)
Skeletal muscle is an essential regulator of energy homeostasis and a potent coordinator of exercise-induced adaptations in other organs including the liver, fat or the brain. Skeletal muscle-initiated crosstalk with other tissues is accomplished though the secretion of myokines, protein hormones which can exert autocrine, paracrine and long-distance endocrine effects. In addition, the enhanced release or uptake of metabolites from and into contracting muscle cells, respectively, likewise can act as a powerful mediator of tissue interactions, in particular in regard to the central nervous system. The present review will discuss the current stage of knowledge regarding how exercise and the muscle secretome improve a broad range of brain functions related to vascularization, neuroplasticity, memory, sleep and mood. Even though the molecular and cellular mechanisms underlying the communication between muscle and brain is still poorly understood, physical activity represents one of the most effective strategies to reduce the prevalence and incidence of depression, cognitive, metabolic or degenerative neuronal disorders, and thus warrants further study.